Cervical pain in individuals with and without temporomandibular disorders - Lilian Gerdi Kittel Ries; Fausto Bérzin (Universidade Estadual de Campinas, 2016)
The objective of this study was to evaluate the association of the Temporomandibular Disorder (TMD) with the presence of pain in the cervical region, as well as to evaluate the involvement of Sternocleidomastoid (SCM) muscle during the activity of the temporal and masseter muscles during dental clenching. 40 female volunteers aged between 18 and 41 years, distributed into a control group and TMD group were enrolled in this study. Clinical examinations of the craniomandibular system and of the neck were performed. Myoelectric activity of the temporalis, masseter and SCM muscle was registered during the mandibular rest position and during the contraction in maximal intercuspal position. The results show to the existence of association between the groups and the presence of cervical pain. It was registered bigger myoelectric activity in SCM muscle during the contraction in maximal intercuspal position than mandibular rest position. The results of this study indicate that individuals with TMD present more pain in the cervical region. The presence of compensatory strategies represents a mechanism necessary to find stability for the mandibular and cervical region during the mandibular movements.